Chemosensor development for cobalt ion recognition using 2-acetylpyrazine thiosemicarbazone: experimental and theoretical approach - Ismail, Hakimah; Ahmad, Mohammad Norazmi; Abdullah, Erna Normaya (2019)
A selective and sensitive chemosensor for recognizing Co2+ in water sample was optimized from a heterocyclic thiosemicarbazone derivative named 2-acetylpyrazine thiosemicarbazone (AT). The optimization of AT as chemosensor was conducted through RSM experiments using UV- Vis spectroscopy. The interaction between AT and Co2+ was found to be optimum in 8:2 v/v DMSO/water at pH 5.3, 100:70 μM AT/Co2+ concentration and 15 minutes reaction time. AT- Co2+ interaction showed colorimetric response from colourless to orange, together with peak- shifting in the absorption spectra from 327 nm to 450 nm. The detection limit of AT towards Co2+ was found to be 3.75 μM while the binding stoichiometry of AT-Co2+ was 2:1. The practicality of AT as chemosensor was tested using three different water samples spiked with Co2+ in the optimized condition. The chemical interaction between AT and Co2+ was further studied through computational studies. DFT calculations for molecular electron potential (MEP), Fukui function and HOMO-LUMO interaction were used to support the experimental results.